Escape from L.A. [videorecording (Blu-Ray)] - Russell, Kurt; Russell, Kurt; Russell, Kurt; Buscemi, Steve, 1957-; Fonda, Peter, 1940-2019; Robertson, Cliff, 1923-2011; Grier, Pam, 1949-; Keach, Stacy; Hill, Debra; Hill, Debra; Carpenter, John, 1948-; Carpenter, John, 1948- (Paramount Home Entertainment, 2017)
Snake Plissken is back, this time in L.A., a gang-infested island. His job is to find a doomsday device and return it to get the antidote for a virus that was injected into him. Includes theatrical trailer.